Sepsis neonatal atau biasa dikenal dengan sepsis neonatorum merupakan infeksi yang melibatkan seluruh aliran darah dan semua organ-organ pada bayi baru lahir yang berusia kurang dari 28 hari. Penyakit ini masih menjadi penyebab utama morbiditas dan mort - Sabila, Ghina; Apriliana, Ety; Islamy, Suryadi; Sari, Ratna Dewi Puspita (CV. Jasa Sukses Abadi, 2024)
Neonatal sepsis is a systemic infection that involves the entire bloodstream and organs of newborns, making it one of the leading causes of neonatal morbidity and mortality, particularly in low- and middle-income countries. Neonatal sepsis is classified into early-onset sepsis (EOS) and late-onset sepsis (LOS), with varying etiologies involving gram-positive bacteria, gram-negative bacteria, and fungi. This article aims to provide a comprehensive review of the etiology, risk factors, diagnosis, and management of neonatal sepsis using an evidence-based approach. This article is based on an analysis of current literature relevant to the epidemiology, pathogenesis, and treatment of neonatal sepsis. EOS is primarily caused by vertical transmission of infection during delivery, with Group B Streptococcus (GBS) as the leading cause, while LOS is often associated with nosocomial infections caused by Staphylococcus epidermidis. Risk factors include prematurity, low birth weight, invasive procedures, and poor infection control. Management involves the administration of broad-spectrum empirical antibiotics within one hour of suspected sepsis, tailored to culture results. A holistic approach, including NICU care, family education, and optimization of infection prevention, has been shown to effectively reduce morbidity and mortality. Neonatal sepsis remains a significant challenge in perinatology, necessitating comprehensive management with an evidence-based approach encompassing timely antibiotic therapy, nosocomial infection control, and family education to improve neonatal outcomes. Preventive efforts, such as enhancing perinatal hygiene and neonatal care, must be optimized to reduce the incidence of neonatal sepsis.